Study of Urban Growth Center Development Factors and Simulation The Mamminasata Urban Area - Emil Salim Rasyidi; Jumadil; Syafri; Rahmawati Rahman; Rusneni; Hamsinah; Muh. Khalil Jibran (Postgraduate, University of Mataram, 2024)
Urban growth starts from a center and affects the surrounding areas, this is due to the emergence of additional centers that will each function as growth poles, to study the dynamics related to urban growth center information, several data and extraction and analysis methods are needed. This study examines several methods of extracting information on urban growth centers from Landsat 8 OLI/TIRS in 2013 and 2023 by utilizing the spectral resolution of Landsat imagery in the Mamminasata area, and integrating spatial modeling to simulate the growth centers of the Mamminasata area in the next 10 years (2043). The results of this research classification method show an accuracy rate of 71.48%. The results of the determinant factor test show that the most influential factors are the distance from the center of shops, slope, then the distance from the university, and the distance from the main road in 2013-2023 Mamminasata Urban Area. The results of this variable drive test are then used in spatial simulations using the markov chain simulation method in the LCM module and show an increase in the area of the growth center in the Mamminasata region, for the entire scope of the Mamminasata region, the Makassar City area shows the highest intensity of regional growth centers and becomes the center of growth in the Mamminasata urban area. The planning concept applied to the results of this study is based on resources, geographic location, and factors affecting the growth center.